Influence of Yb:Hf Ratio on Ytterbium Hafnate/Molten Silicate (CMAS) Reactivity1. Issue 2 (9th October 2015) - Poerschke, David L.; Seward, Gareth G. E.; Levi, Carlos G.
Abstract : This study investigated the influence of YbO1.5 concentration on the reactivity between YbO1.5 –HfO2 thermal barrier coating (TBC) materials and silicate melts [calcium–magnesium aluminosilicate (CMAS), specifically 33CaO–9MgO–13AlO1.5 –45SiO2, all in mol%]. Three thermal barrier oxides (TBO) with YbO1.5 concentration between 30 and 80 mol% were tested at 1300°C and 1500°C. Porous pellets were used to study reaction layer growth and the behavior within infiltrated porosity. Complementary experiments examined the phase equilibria in melts containing varying quantities of the candidate TBOs. The effectiveness of reactive crystallization to limit interaction depth increased with the YbO1.5 concentration in the TBO. The results indicate that the TBO must contain sufficient YbO1.5 to satisfy the equilibrium between the melt and HfO2 ‐based fluorite phase before YbO1.5 ‐bearing silicates can precipitate. Increasing the YbO1.5 availability leads to the crystallization of apatite, garnet, silicocarnotite, and/or cuspidine (alumino)silicates. Apatite was observed at 1300°C and 1500°C, garnet and silicocarnotite only appeared at 1300°C, and cuspidine was only evident at 1500°C. The implications for the design of CMAS‐resistant coatings are discussed in the context of the experimental results.